Biomechanical investigation of a novel hybrid dorsal double plating for distal radius fractures by integrating topology optimization and finite element analysis. Issue 6 (June 2020) - Liu, Hsuan Chih; Jiang, Jin-Siou; Lin, Chun-Li
Highlights: Integrating FE analysis and topology optimization to design a novel hybrid dorsal double plating (HDDP) for distal radius fracture. The novel HDDP profile was presented as a "Y" shape and retained three-column features to enhance biomechanical strength. The novel HDDP demonstrated better resistance to functional loads and provided enough screw fixations at the articular surface. The novel HDDP can be placed through the standard dorsal approach to use minimal invasive surgical technique and eliminated tendon irritation. Abstract: Background: Currently available dorsal locking plates for the treatment of distal radius fractures are far less then volar locking plates, and there is limited evidence about biomechanical strength of dorsal plates. The aim of this study is to develop a novel hybrid dorsal double plating, which enhance biomechanical strength in the articular fixation region and achieve the minimally invasive surgical technique requirement of distal radius fracture treatment by combining weighted topology optimization and finite element (FE) analysis Methods: A dorsal template bone plate design (based on dorsal double plating (DDP)) was constructed to perform weighted topology optimization and FE analysis under six fracture models with 50%, 30%, and 20% weighting of the joint subjected to axial, bending, and torsion moments, respectively. A novel hybrid dorsal double plating (HDDP) was generated using the union of six single dorsal plates to subtract the intersection of the original template dorsal model. A 100 N axial load with 1 Nm bending and torsion moments were applied at the end of the distal radius onto six fracture FE models to investigate the biomechanical differences between the DDP and HDDP approaches. Results: Results of weighted topology optimization showed that the profile of the HDDP presented a "Y" shape. Simulation results showed that the bone plate stress values for the distal radius fractures fixed with HDDP was much smaller than those with DDP regardless of the type of bone fractures and load conditions. The maximum bone stress value of the DDP approach was much higher than that of HDDP when the distal radius was a complete sagittal articular fracture and partial articular fracture involving lunate fossa. The corresponding maximum bone stress values for different loads might be higher than the ultimate strength of bone (150  MPa) and induced the risk of future bone fractures. Conclusions: It is concluded that the novel HDDP demonstrated better resistance to functional loads, provided sufficient screw fixation at the articular surface, and can be placed on the dorsal site of the distal radius through the standard dorsal approach to minimize invasive surgeries and eliminate tendon irritations.